2004
DOI: 10.4049/jimmunol.172.2.1169
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Resists Human Defensins by Production of Staphylokinase, a Novel Bacterial Evasion Mechanism

Abstract: α-Defensins are peptides secreted by polymorphonuclear cells and provide antimicrobial protection mediated by disruption of the integrity of bacterial cell walls. Staphylokinase is an exoprotein produced by Staphylococcus aureus, which activates host plasminogen. In this study, we analyzed the impact of interaction between α-defensins and staphylokinase on staphylococcal growth. We observed that staphylokinase induced extracellular release of α-defensins from polymorphonuclear cells. Moreover, a direct binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
190
2
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(193 citation statements)
references
References 31 publications
0
190
2
1
Order By: Relevance
“…To date, in S. aureus, three types of mechanism that affect susceptibility to antimicrobial peptides have been identified. These are (1) trapping defensins by binding to staphylokinase (Braff et al, 2007;Jin et al, 2004), (2) digestion of peptides by proteinase (Sieprawska-Lupa et al, 2004), and (3) changing the bacterial cell surface charge via dlt and mprF (Li et al, 2007a;Peschel et al, 1999Peschel et al, , 2001. mprF was first identified as fmtC, which was shown to affect the meticillin-resistance level in MRSA (Komatsuzawa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To date, in S. aureus, three types of mechanism that affect susceptibility to antimicrobial peptides have been identified. These are (1) trapping defensins by binding to staphylokinase (Braff et al, 2007;Jin et al, 2004), (2) digestion of peptides by proteinase (Sieprawska-Lupa et al, 2004), and (3) changing the bacterial cell surface charge via dlt and mprF (Li et al, 2007a;Peschel et al, 1999Peschel et al, , 2001. mprF was first identified as fmtC, which was shown to affect the meticillin-resistance level in MRSA (Komatsuzawa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is now appreciated that SK is independently able to directly bind α-defensins produced by human neutrophils, inhibiting their bactericidal activity [36]. Testing of a panel of SA strains found that those producing SK were resistant to α-defensins, and that addition of purified SK to SK-negative SA cultures rescued them from α-defensin killing [36].…”
Section: Infections Due To Microbial Resistance To the Innate Immune mentioning
confidence: 99%
“…It is now appreciated that SK is independently able to directly bind α-defensins produced by human neutrophils, inhibiting their bactericidal activity [36]. Testing of a panel of SA strains found that those producing SK were resistant to α-defensins, and that addition of purified SK to SK-negative SA cultures rescued them from α-defensin killing [36]. Interestingly, SA upregulates cathelicidin expression during infection, and the binding of cathelicidin to SK augments the ability of this virulence factor to activate plasminogen, promote fibrinolysis, and allow bacterial dissemination [37].…”
Section: Infections Due To Microbial Resistance To the Innate Immune mentioning
confidence: 99%
“…Both mechanisms increased susceptibility to the peptides [124,127]. Staphylokinase inhibits the antibacterial activity of the α-defensins by reducing the binding affinity of these peptides [128]. Therefore, it is possible that up-or down-regulation of these factors in S. aureus may influence the susceptibilities.…”
Section: Anti-s Aureus Activity Of Anti-microbial Peptidesmentioning
confidence: 99%